The Growing Accountability Agenda in Tertiary Education : Progress or Mixed Blessing? - Salmi, Jamil (World Bank, Washington, DC, 2014)
The purpose of this paper is to examine the accountability agenda in the tertiary education. Author proposes three principles of good accountability. First, accountability should not focus on the way institutions operate, but on the results that they actually achieve. Second, accountability works better when it is experienced in a constructive way, rather than being imposed in an inquisition-like mode. Tertiary education institutions are more likely to appreciate the value of reporting obligations if their relationship with stakeholders, especially government authorities, is based on positive incentives rather than punitive measures. Third, the most effective accountability mechanisms are those that are mutually agreed or are voluntarily embraced by tertiary education institutions. The paper concludes that the successful evolution of tertiary education hinges on finding an appropriate balance between credible accountability practices and favorable autonomy conditions.